Interdisciplinary approach for pathologic tooth migration in advanced periodontal disease patient - Marie Louisa (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Recent treatment trends have included an interdisciplinary approach to cases and have stressed the importance of orthodontic treatment in optimising the prognosis for patients with periodontal disease. Orthodontic intrusion is a reliable method to improve periodontal support as research has previously documented. Purpose: This case study demonstrates an interdisciplinary approach to treating a patient with moderately advanced periodontitis disease and pathologic tooth migration (PTM) of the upper left central incisor to enhance structure, function and aesthetics. Case: A 46-year-old systemically healthy male patient came with a chief complaint of a protruding and elongated tooth. Clinical examination showed a mobile, extruded incisor along with bleeding on probing and suppuration. Periodontal and radiographic examinations showed generalised horizontal bone loss combined with infrabony defects at the pathologically migrated upper left central incisor. Case Management: Periodontal inflammation was treated with a combination of nonsurgical and surgical therapy. Afterward, orthodontic treatment was done using a self-ligating system. The intrusion of a pathologically extruded tooth improved infrabony defects, creating a favourable bone level and probing depth. Conclusion: The combination of periodontal–orthodontic therapy achieves satisfactory outcomes if periodontal inflammation is controlled, physiologic forces are used, and oral hygiene is maintained throughout therapy.